2016
DOI: 10.1016/j.neuropharm.2016.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Role for serotonin2A (5-HT2A) and 2C (5-HT2C) receptors in experimental absence seizures

Abstract: Absence seizures (ASs) are the hallmark of childhood/juvenile absence epilepsy. Monotherapy with first-line anti-absence drugs only controls ASs in 50% of patients, indicating the need for novel therapeutic targets. Since serotonin family-2 receptors (5-HT2Rs) are known to modulate neuronal activity in the cortico-thalamo-cortical loop, the main network involved in AS generation, we investigated the effect of selective 5-HT2AR and 5-HT2CR ligands on ASs in the Genetic Absence Epilepsy Rats from Strasbourg (GAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 103 publications
(144 reference statements)
2
53
0
1
Order By: Relevance
“…Some typical 5-HT 2C R agonists dose-dependently suppressed absence seizures in the Genetic Absence Epilepsy Rats from Strasbourg (GAERS), a well-established polygenic rat model of absence epilepsy and non-convulsive seizures; these effects were prevented when administering a selective 5-HT 2 C R antagonist, indicating the potential of selective 5-HT 2C R agonists as novel anti-absence drugs (Venzi et al, 2016). Experiments on Wistar Albino Glaxo rats from Rijswijk (WAG/Rij) rats, another polygenic rat model of absence epilepsy, have found that mCPP decreased spike-wave discharges (SWDs) cumulative duration via the activation of 5-HT 2C Rs (Jakus et al, 2003).…”
Section: Monoamines In Epilepsy: Preclinical and Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Some typical 5-HT 2C R agonists dose-dependently suppressed absence seizures in the Genetic Absence Epilepsy Rats from Strasbourg (GAERS), a well-established polygenic rat model of absence epilepsy and non-convulsive seizures; these effects were prevented when administering a selective 5-HT 2 C R antagonist, indicating the potential of selective 5-HT 2C R agonists as novel anti-absence drugs (Venzi et al, 2016). Experiments on Wistar Albino Glaxo rats from Rijswijk (WAG/Rij) rats, another polygenic rat model of absence epilepsy, have found that mCPP decreased spike-wave discharges (SWDs) cumulative duration via the activation of 5-HT 2C Rs (Jakus et al, 2003).…”
Section: Monoamines In Epilepsy: Preclinical and Clinical Evidencementioning
confidence: 99%
“…As both epilepsy and monoamine-based neuropsychiatric disorders are complex diseases that imply changes in multiple neurotransmitters and both neuronal and glial cells activity, a comprehensive understanding of the underlying mechanisms is still in its infancy. Nevertheless, this evidence of dual link between these two disorders suggest that drugs targeting monoamines may be useful for both epilepsy and its neuropsychiatric comorbidities (Guiard and Di Giovanni, 2015; Venzi et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…19,20 The antiseizure activity of pulicatin B ( 1 ) was tested in mice at the NIH/NINDS Epilepsy Therapy Screening program contract site at the University of Utah. Four mice each were used for initial screening in the maximal electroshock seizure (MES) 21,22 and 6 Hz psychomotor seizure tests 23 (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…The electrical stimulus in the MES test (50 mA, 60 Hz, 0.2 sec) was delivered via corneal electrodes by an apparatus similar to that originally described by Woodbury and Davenport. 19 Abolition of the hind leg tonic extensor component is taken as the endpoint for this test. Efficacy on four mice was compared by evaluating the following i.p.…”
Section: Methodsmentioning
confidence: 99%
“…5-HT2CR are expressed in the amygdala, and fMRI data have demonstrated that 5-HT 2C R agonists lead to its neuronal activation (Hackler et al 2007). Other therapeutic indications relate to obesity and possibly epilepsy Brennan et al 1997;Heisler et al 1998;2007a; as observed in the first series of receptor transgenic mice and later with 5-HT2CR selective ligands (Venzi et al 2016;Bagdy et al 2007;Jakus et al 2003;Isaac 2005). It is still a challenge to synthesise 5-HT 2CR selective agonists, devoid of significant interactions with the other 5-HT2 receptor subtypes, since 5-HT2B receptor activation results in detrimental cardiac effects such as valvulopathies (see Fitzgerald et al 2000;Roth 2007), whereas 5-HT2AR activation leads to hallucinations (Nichols 2004).…”
Section: The Modern Era: Therapeutic Considerationsmentioning
confidence: 99%